2018
DOI: 10.1590/0100-3984.2017.0025
|View full text |Cite
|
Sign up to set email alerts
|

Suspicious amorphous microcalcifications detected on full-field digital mammography: correlation with histopathology

Abstract: ObjectiveTo evaluate suspicious amorphous calcifications diagnosed on full-field digital mammography (FFDM) and establish correlations with histopathology findings.Materials and MethodsThis was a retrospective study of 78 suspicious amorphous calcifications (all classified as BI-RADS® 4) detected on FFDM. Vacuum-assisted breast biopsy (VABB) was performed. The histopathological classification of VABB core samples was as follows: pB2 (benign); pB3 (uncertain malignant potential); pB4 (suspicion of malignancy); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
3
1
1
1
Order By: Relevance
“…Whereas, for malignant cases, a significant difference was not observed. The malignancy rates reported in the previous literatures ranged from 10% (8/78) to 39% (41/105) [ [31] , [32] , [33] ], which was consistent with our result. In our study, 98 (31%) sites of suspicious calcifications were proved malignant and 214 (69%) were benign.…”
Section: Discussionsupporting
confidence: 93%
“…Whereas, for malignant cases, a significant difference was not observed. The malignancy rates reported in the previous literatures ranged from 10% (8/78) to 39% (41/105) [ [31] , [32] , [33] ], which was consistent with our result. In our study, 98 (31%) sites of suspicious calcifications were proved malignant and 214 (69%) were benign.…”
Section: Discussionsupporting
confidence: 93%
“…Age and menopausal status have always been important risk factors for the benign and malignant calcifications of the breast, which have been distinguished in BI-RADS category 4 calcifications (14) and amorphous calcifications (4). In this study, age group and menopausal status were also found to be malignancy risk factors, and elderly women (aged ≥60 years) had a higher malignancy rate than younger women, which is consistent with the literature on amorphous calcifications (4,23).…”
Section: Discussionsupporting
confidence: 89%
“…Similar PPV values—7.9%, 7.1%, 10.3%, and 10.5%—were reported, respectively, by Kim et al. ( 6 ) , Metaxa et al ( 7 ) , Oligane et al ( 2 ) , and Ferreira et al ( 8 ) . This risk stratification brings amorphous calcifications closer to BI-RADS category 4a than category 4b (as currently suggested).…”
Section: Discussionsupporting
confidence: 84%
“…Although the rate of detection of amorphous calcifications has increased with the use of digital mammography and specific medical monitors, the management of this subgroup of calcifications can be challenging. It is not uncommon for amorphous calcifications to be identified only on magnified images, in only one view, or even not defined in the stereotactic window on stereotaxic devices or tables, making it impossible to perform percutaneous biopsy or the preoperative marking process ( 4 , 5 , 6 , 7 , 8 , 9 ) .…”
Section: Introductionmentioning
confidence: 99%